Frequency and risk factor analysis of cognitive and anxiety-depressive disorders in patients with amyotrophic lateral sclerosis/motor neuron disease - Cui F (Dove Medical Press, 2015)
Fang Cui, Wenjia Zhu, Zhibin Zhou, Yuting Ren, Yifan Li, Mao Li, Yunyun Huo, Xusheng Huang Department of Neurology, Chinese PLA General Hospital, Beijing, People’s Republic of China Objectives: To examine the frequency and risk factors of cognitive and anxiety-depressive disorders in patients with amyotrophic lateral sclerosis/motor neuron disease (ALS/MND). Methods: This was an observational study of 100 ALS/MND patients treated at our hospital outpatient and inpatient departments between January 2009 and April 2010 and 100 matched healthy controls. Subjects were surveyed using Mini Mental State Examination (MMSE), Zung Self-Rating Anxiety Scale (SAS), and Zung Self-Rating Depression Scale (SDS). Patient neurological status was graded by the ALS Functional Rating Scale (ALSFRS). Multivariate linear regression was used to identify factors associated with the MMSE, SAS, SDS, and ALSFRS scores. Results: Patients had significantly lower MMSE scores than controls (P<0.05). MMSE score did not differ by sex or age (<50/≥50 years) (P>0.05). Patients with higher educational level (college and above), shorter disease course (<2 years), and lower ALSFRS score (<20) had significantly higher MMSE scores (all P<0.05). Multivariate analysis revealed that higher education, shorter disease course, and lower ALSFRS score were independent predictors of better cognitive function (higher MMSE score). Patients had significantly higher mean SAS and SDS total scores than controls (both P<0.05), indicating higher subjective anxiety and depression. Female patients, patients with higher education, and those with higher ALSFRS scores had significantly higher SAS and SDS scores (all P<0.05). Age, occupation, diagnostic classification, disease duration, and disease awareness did not influence SAS or SDS scores. Multivariate analysis indicated that lower education and lower ALSFRS were protective factors against anxiety and depression. Conclusion: The frequency of anxiety-depressive disorders was high among patients with ALS/MND. High educational level, short course of disease, and lower ALSFRS were associated with preserved cognitive function. Female sex, higher education, and lower ALSFRS score conferred a greater risk of anxiety and depression. Tailored pharmacotherapy and psychological interventions may help in reducing anxiety and depression in these patients. Keywords: motor neuron disease, amyotrophic lateral sclerosis, cross-sectional study, anxiety, depression